(untitled) (Società e diritti, 2025)
The Public Legal Advisory Offices are a mode of experiential learning, both for students and for the Faculty-Tutors of the Law Faculties. These forms of practical-experiential learning, emerged in the sixties in the Law Schools of the United States, then moved to other contexts, such as Latin America and Europe. In the Law Faculties of Argentina, Legal Offices arrived in the 1990s informally with different characteristics, introduced by graduate students trained in the United States of America who returned to the country (Bonilla Maldonado, Daniel;2018). From those beginnings to the present, the Legal Offices in Argentina have evolved, not exempt of questioning by the Bar Associations. In the Faculty of Law of the Universidad Nacional de Córdoba (UNC) Argentina, there is no free legal consultancy as a way of practical educationthe National University of Cordoba has a free legal office for the university community. It should be pointed out that the curricula of the Career Law Course Plan include subjects relating to professional practice. This article reflects on the Legal Offices, the positive and negative aspects of them, the gratuity or lack of onerousness, the functions of mere advice or legal sponsorship, interdisciplinarity, the objectives proposed, the possibility of access to justice for the vulnerable, the search for social justice, the subjects covered, the conditions that must have those who apply for legal services, among others. We present the results of an exploratory survey carried out in June 2024 among law students of the Faculty of Law of the National University of Córdoba (Argentina) about legal consultancies.